Nexus Between Monetary Instruments and Bank Credit Distribution: Evidence from ASEAN Countries - Rani Septiani; Dwi Wulandari; Bagus Shandy Narmaditya; Putra Hilmi Prayitno (Indonesian Economic Review, 2022)
The aim of this study was to examine the relationship between monetary indicators and bank credit distribution, including inflation, interest rate, and exchange rate in seven ASEAN countries namely Brunei, Indonesia, Philippine, Malaysia, Singapore, Thailand, and Vietnam. This study applied a quantitative approach by engaging multiple regression analysis with panel data using cross-section data from 2012 to 2018. The data in this research was secondary data which gathered from the World Bank website. The findings of this study showed that inflation and interest rate had a negative influence on bank credit distribution, while the exchange rate had a positive effect on bank credit distribution. The study’s result also showed that variable inflation, interest rate, and the exchange rate had a simultaneous effect on bank credit distribution in seven ASEAN countries. These results suggest that for the policy makers in each ASEAN country should be able to consider a lending regulation.